2018
DOI: 10.3390/languages3030026
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring L1-English L2-Spanish Code-Switching: The Role of Exposure to Language Mixing

Abstract: This paper explores the code-switching behavior of second language (L2) bilinguals as a lens into the development of their L2 linguistic systems. Specifically, it investigates the acceptability judgments of L1-English L2-Spanish bilinguals on intra-sentential code-switching, comparing those judgments to a group of Spanish–English bilinguals who acquired both languages as an L1. The particular issues of proficiency and bilingual language behavior are analyzed, testing whether either factor has an effect on L2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…CS use, for instance, was significant in the low proficiency groups, but the non-CS group of higher proficiency fell somewhere in between the two low proficiency groups in their ratings. Koronkiewicz (2018), thus, concludes both proficiency and CS use are important in the acquisition of CS. In general, in Giancaspro (2013Giancaspro ( , 2015 and Koronkiewicz (2018), participants showed evidence of acquisition of CS.…”
Section: Cs Research With L2ersmentioning
confidence: 85%
See 2 more Smart Citations
“…CS use, for instance, was significant in the low proficiency groups, but the non-CS group of higher proficiency fell somewhere in between the two low proficiency groups in their ratings. Koronkiewicz (2018), thus, concludes both proficiency and CS use are important in the acquisition of CS. In general, in Giancaspro (2013Giancaspro ( , 2015 and Koronkiewicz (2018), participants showed evidence of acquisition of CS.…”
Section: Cs Research With L2ersmentioning
confidence: 85%
“…Koronkiewicz (2018), thus, concludes both proficiency and CS use are important in the acquisition of CS. In general, in Giancaspro (2013Giancaspro ( , 2015 and Koronkiewicz (2018), participants showed evidence of acquisition of CS. These results are consistent with Toribio's (2001) hypothesis that once the related grammar is acquired in Spanish, Spanish L2ers can distinguish grammatical and ungrammatical structures.…”
Section: Cs Research With L2ersmentioning
confidence: 85%
See 1 more Smart Citation
“…Both forced-choice and scalar acceptability judgments have been employed in code-switching research, and although direct comparison with the Quichua–Media Lengua data can only be approximated, the fact that the Ecuadorian participants did not categorically reject all nominally disallowed code-switches is not out of line with the results of other studies, even those involving languages with considerable morphosyntactic differences. This includes Aguirre (1981, p. 304; 1985, p. 65) and Koronkiewicz (2014, pp. 83–99 for Spanish–English switches after subject pronouns, Ebert (2014, pp.…”
Section: Resultsmentioning
confidence: 99%
“…In Spanish–English code-switching, subject pronoun switching is usually unacceptable, due to the status of English as a non-null subject language, but switching can occur with coordinated pronouns, hanging topics, clefting, modification, and prosodic stress (Koronkiewicz, 2012, pp. 1–2; 2014), all cases in which overt pronouns are obligatory in Spanish. Gumperz (1977, p. 26) has suggested that reported constraints against switching between pronouns and verbs may have to do with the fact that many pronouns are short, although when they can be contrasted or stressed switching may occur.…”
Section: Discussionmentioning
confidence: 99%